Does relative performance information lower group morale? - Lea Heursen (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
In many organizations, productivity relies not just on individual effort but also on group morale, that is, the willingness of co-workers to help each other perform better at work. Relative performance evaluations (RPE) are known to increase individual work morale but may negatively affect group morale because they create a sense of competition among members of a reference group. In a novel experiment, I vary whether or not members of a reference group obtain relative performance information on a task that is relevant for their social image or selfimage, a general knowledge test. I measure how this affects the subsequent willingness to help the productivity of others by sharing knowledge with them at a personal cost. I find that RPE cause members of a reference group to compete as intensely as under relative pay, compared to a baseline with no relative performance information and fixed piece-rates. It also increases the perceived social distance between them. Yet, I show that even after a performance competition, individuals are willing to help the productivity of others in the group. These findings advance our understanding of how relative concerns among co-workers affect the way they work together.
Keywords: D23; C92; J24; D91; 330; relative performance information; rank feedback; social incentives; on-the-job help; group productivity; social and self-image; experiment